Elaboration and characterization of the electrodeposited phosphates masses doped with various ions on stainless steel - Totea, G. (2014)
The present paper is focused on elaboration of phosphate masses with good molar ratios on SS 316L, with fluoride, Zn2+ and Cu2+ as dopant ions, using an electrochemical procedure and also the attempt to select the best conditions for stainless steel. The surface was characterized using X-ray difraction, AFM and contact angle measurements. X-ray has evidenced crystaline phases, contact angle measurements has established the balance hydrophyl-hydrophob and AFM established roughness values. The inductively coupled spectrometry (ICP-MS) has quantified the amount of cooper and zinc ions released. In order to be used in biomedical applications hemolysis and antibacterial tests have been performed.